Cognitive communication disorders - Kimbarow, Michael L., 1953- (Plural Publishing, Inc., 2021)
"For graduate courses that address cognitively based communication disorders, this textbook presents a comprehensive discussion of cognitive processes and deficits, including attention, memory, executive functions, right hemisphere brain damage, dementia, combat-related mild traumatic brain injury, and traumatic brain injury and the impact that deficits in these cognitive domains may have on language and communication."--Publisher